2020
DOI: 10.1088/1748-0221/15/04/c04003
|View full text |Cite
|
Sign up to set email alerts
|

Transport of accelerated electrons through dielectric nanochannels in PET films

Abstract: We investigated the transmission of 10 keV electrons through insulating nanocapillaries of various diameters from 200 nm up to 800 nm with high intensity current (∼56 nA/mm 2 ). We demonstrate a way to identify the quasi-elastic transmission from the total transmission by looking at the characteristic X-rays induced by the transmitted electrons. It shows that the transmitted electrons follow the geometrical transmission with a little deviation. The portion of the nearly elastic transmission is found to be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…It is important in the experiment to determine the energy state of electrons transmitted through the channel, in particular, to estimate the fraction of electrons whose energy loss is less than 1 keV, i.e., 10% of the initial energy of the beam electrons. Estimation was carried out by the method suggested by the authors described in detail in [17]. The principle of the method lies in the comparison of the spectra of emission generated in the metal target upon its exposure to an incident and transmitted beam of electrons 7, which is generated in the metal (copper) plate 10 upon its exposure to electrons.…”
Section: Methodsmentioning
confidence: 99%
“…It is important in the experiment to determine the energy state of electrons transmitted through the channel, in particular, to estimate the fraction of electrons whose energy loss is less than 1 keV, i.e., 10% of the initial energy of the beam electrons. Estimation was carried out by the method suggested by the authors described in detail in [17]. The principle of the method lies in the comparison of the spectra of emission generated in the metal target upon its exposure to an incident and transmitted beam of electrons 7, which is generated in the metal (copper) plate 10 upon its exposure to electrons.…”
Section: Methodsmentioning
confidence: 99%
“…Измерение спектра выполнялось для оценки доли электронов пучка, испытавших потери менее 1 keV. Метод такой оценки подробно описан в [9]. Одновременно проводится измерение тока прошедшего или прямого пучка с помощью пикоамперметра Keithley 6482 (11 на рис.…”
Section: X-ray Detectorunclassified
“…Additionally, it has been demonstrated that dielectric capillaries can transmit ion beams without any change in both the ion kinetic energy and the ion charge [66]. Capillary guiding peculiarities have been also studied for electron beams, revealing similar elastic and inelastic features of scattering by the inner capillary surface, while a time evolution of transmitted intensity for electrons remains essentially different from that of ions [67][68][69][70][71][72][73][74][75][76][77].…”
Section: Introductionmentioning
confidence: 99%